Efforts To Maintain Public Health During The Covid-19 Pandemic With Islamic Education - Mhd Azis Satria; Dhiauddin Tanjung; Muhammad Farhan; Nurul Amalia; Nabila Zahra Siregar (At-Tarbiyat, 2022)
Abstract This study discusses the correlation between Islamic education derived from the Qur'an, Sunnah and Ijma regarding efforts to maintain public health. The research method used is qualitative research with the type of field research and phenomenological approach. This study provides evidence that there is a positive relationship between Islamic education and public health patterns, especially in Islamic values ​​and public health. Especially now that the whole world is experiencing an outbreak of the COVID-19 pandemic and of course this is a big problem for all countries in the world, including our country Indonesia. The spread of COVID-19 is so fast and deadly. Of course, the contribution of the government and all communities is needed to be able to understand about the transmission of the covid-19 outbreak. The results of the research in the sub-district of Medan Marelan are the community's efforts to maintain health during the pandemic by carrying out routine tests in health services and not forgetting to also implement prokes in the community and implement a clean and healthy lifestyle as recommended by the government and of course in accordance with Islam